COVID 19 and Spanish flu pandemics: All it changes, nothing changes: COVID 19 epidemic - Franchini, Antonia Francesca; Auxilia, Francesco; Galimberti, Paolo M.; Piga, Maria Antonella; Castaldi, Silvana; Porro, Alessandro (Acta Biomedica Atenei Parmensis, 2020)
The Corona Virus 19 (COVID 19) epidemic is an infectious disease which was declared as a pandemic and hit all the Countries, all over the world, from the beginning of the year 2020. There are many similarities between the COVID 19 epidemic and the Spanish flu epidemic. We considered some preventive measures which do not change in the two epidemics.